Evaluation of Coal Seam Gas Drainability for Outburst-Prone and High-CO2-Containing Coal Seam - Lei Zhang; Ting Ren; Naj Aziz; Cun Zhang (Geofluids)
This paper presents the results of an evaluation study of gas drainability in the Bulli seam in the Southern Coalfield of the Sydney Basin, NSW, Australia, where the coal seam gas (CSG) contains a high proportion of carbon dioxide (CO2). Historically the gas drainability in some particular areas of this coal seam was found to be particularly poor, which posed a significant challenge to gas predrainage. As a result, a large volume of greenhouse gases were released to the atmosphere during mining of the coal seam. Furthermore, the high gas content associated with the CO2-rich composition also increased the risks of coal and gas outburst incidents, affecting the safety of mining. After systematic literature review of evaluation factors affecting gas drainability, this evaluation study comprehensively analyzed the main critical factors, including the geology of the area, the coal cleat system, coal microstructure, coal permeability, coal sorption capacity, gas content, and gas composition. Field geology analysis showed geological variations that affected the variations of the coal cleat system and CO2 content in the coal seam. Scanning Electron Microscope (SEM) tests showed the tight and less-porous features in hard-to-drain coal samples. The colliery gas database analysis was carried out to assess the impact of gas content and gas composition on the drainability of the coal seam. Laboratory tests showed that the coal seam had a permeability of less than 1 mD and also showed that the coal seam was highly undersaturated, especially with high CO2 content.